2010
DOI: 10.1073/pnas.0905745107
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor gamma activation is required for maintenance of innate antimicrobial immunity in the colon

Abstract: Crohn's disease (CD), a major form of human inflammatory bowel disease, is characterized by primary immunodeficiencies. The nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) is essential for intestinal homeostasis in response to both dietaryand microbiota-derived signals. Its role in host defense remains unknown, however. We show that PPARγ functions as an antimicrobial factor by maintaining constitutive epithelial expression of a subset of β-defensin in the colon, which includes mDefB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 25 publications
2
137
0
4
Order By: Relevance
“…PPAR-γ acts as a main lipid sensor in the SI. It has previously been shown to be a major regulator of mucosal defenses (58,59). We observed that HF diet down-regulated Ppar-γ gene expression by 1.84-fold (Fig.…”
Section: Dysregulation Of the Ppar-γ Pathway By Hf Diet Accounts Forsupporting
confidence: 54%
See 1 more Smart Citation
“…PPAR-γ acts as a main lipid sensor in the SI. It has previously been shown to be a major regulator of mucosal defenses (58,59). We observed that HF diet down-regulated Ppar-γ gene expression by 1.84-fold (Fig.…”
Section: Dysregulation Of the Ppar-γ Pathway By Hf Diet Accounts Forsupporting
confidence: 54%
“…Taken together, these data indicate an association between PPAR-γ and the mucus formation in the ileum. It has also been described that PPAR-γ is a direct regulator of β-defensin expression in the human and mouse colons but not in the mouse ileum (58). However, in the current HF diet model, down-regulation of Ppar-γ was concomitant to down-regulation of major AMP, such as defensins, in the ileum, and when Ppar-γ expression was increased by rosiglitazone, AMP gene expression was also restored.…”
Section: Discussionmentioning
confidence: 63%
“…It is interesting that HBD1 expression seems to be maintained by the peroxisome proliferator-activated receptor gamma (PPARgamma) acting as an antimicrobial factor [55]. In line with this, the colonic mucosa of PPAR-gamma mutant mice showed a reduced killing capacity against Candida albicans, B. fragilis, Enterococcus faecalis and E. coli as compared to wild-type littermates [55].…”
Section: Barrier Dysfunction In Colonic CDmentioning
confidence: 75%
“…12 In addition to the biliary epithelial cells of PBC, a reduction of PPARγ expression in the colonic epithelial mucosa is reportedly associated with the pathogenesis of inflammatory bowel diseases (IBD). [13][14][15][16] Furthermore, the expression of PPARγ is affected by the commensal intestinal flora and ligands (agonists) for PPARγ can attenuate colitis in IBD-model mice, supporting the notion that PPARγ ligands may have salutary effects on IBD. 14,[16][17][18] As for anti-inflammatory activities, the activation of PPARγ by its ligands is shown to inhibit the expression of pro-inflammatory cytokines, the induction of which is mediated via NF-κB and mitogen activated protein kinase (MAPK).…”
Section: Introductionmentioning
confidence: 82%